2003
DOI: 10.1186/bcr751
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cell proliferation (Ki-67) to 99mTc-(V)DMSA uptake in breast cancer

Abstract: Keywords: breast cancer, 99m 99m Tc-(V)DMSA, scintimammography R56 DCIS = ductal carcinoma in situ; ER = estrogen receptor; MIBI = sestamibi; 99m Tc = technetium-99m; (V)DMSA = pentavalent dimercaptosuccinic acid; PR = progesterone receptor. Breast Cancer ResearchVol 6 No 2 Papantoniou et al. Research articleRelationship of cell proliferation (Ki-67) to 99m Tc-(V)DMSA uptake in breast cancer In addition, by multivariate regression analysis, we further isolated those factors with independent associations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14] Technetium 99m pentavalent dimercaptosuccinic acid ( 99m Tc(V)-DMSA) is a well-known cell proliferationseeking radiotracer with affinity for neuroendocrine and soft tissue tumors, such as medullary thyroid carcinoma and lung, breast, brain, and metastatic bone lesions. [15][16][17][18][19][20][21][22][23][24][25][26][27] Based on in vivo scintigraphic studies, we initially suggested that its cellular uptake mechanism is closely related to cellular proliferation, as expressed by the Ki-67 immunohistologic index [28][29][30] and at the same time independent from estrogen receptor (ER) status. 23,24 Denoyer and colleagues elucidated the exact mechanisms: the tracer reflects phosphate ion (Pi) transport and metabolism, entering cancer cells specifically via the type III Na/Pi cotransporter, this uptake being driven by the cellular levels of phosphorylated (ie, activated) focal adhesion kinase (FAK), a keystone of accelerated proliferation.…”
Section: Ncreased Mammographic Breast Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14] Technetium 99m pentavalent dimercaptosuccinic acid ( 99m Tc(V)-DMSA) is a well-known cell proliferationseeking radiotracer with affinity for neuroendocrine and soft tissue tumors, such as medullary thyroid carcinoma and lung, breast, brain, and metastatic bone lesions. [15][16][17][18][19][20][21][22][23][24][25][26][27] Based on in vivo scintigraphic studies, we initially suggested that its cellular uptake mechanism is closely related to cellular proliferation, as expressed by the Ki-67 immunohistologic index [28][29][30] and at the same time independent from estrogen receptor (ER) status. 23,24 Denoyer and colleagues elucidated the exact mechanisms: the tracer reflects phosphate ion (Pi) transport and metabolism, entering cancer cells specifically via the type III Na/Pi cotransporter, this uptake being driven by the cellular levels of phosphorylated (ie, activated) focal adhesion kinase (FAK), a keystone of accelerated proliferation.…”
Section: Ncreased Mammographic Breast Densitymentioning
confidence: 99%
“…26,27 Recent in vivo and in vitro studies have demonstrated its potential to depict increased cellular proliferation not only in invasive carcinoma but also in epithelial hyperplasia of the usual type and in preinvasive mammary lesions (ie, DCIS), independently of the presence of estrogen and progesterone receptors. 15,[26][27][28][29][30][31][32][33] This retrospective study aimed at identifying a possible relationship between mammographic BD and scintimammographic 99m Tc(V)-DMSA uptake in various breast histologies. It also investigated whether women with dense breasts, possibly disclosing or expressing a proliferating potential, could be discriminated visually or on the basis of semiquantitative analysis of 99m Tc(V)-DMSA intensity of uptake and benefit from biopsy and possible proper chemoprophylactic treatment.…”
Section: Ncreased Mammographic Breast Densitymentioning
confidence: 99%
“…Tc-99m (V) DMSA uptake in breast cancer and Ki-67 expression suggests Tc-99m (V) DMSA as a surrogate marker of cell proliferation. [ 71 ] Tc-99m (V) DMSA correlates with tumor aggressiveness and provides important information regarding the correlation of tumor subtype with breast density[ 72 ] [ Table 4 ].…”
Section: Pentavalent Dimercaptosuccinic Acid (Tc-99m (V) Dmsa)mentioning
confidence: 99%
“…In addition, Papantoniou et al (2001) reported that 99m Tc-(V)DMSA uptake by breast tumors and several breast lesions is related to the mitotic activity and the cellular proliferation of breast tumors or lesions. Recently a strong correlation between 99m Tc-(V)DMSA uptake and cellular proliferation, as measured by Ki-67 expression (Ki-67, a monoclonal antibody that recognizes a labile epitope on a nuclear antigen expressed in cycling cells but not quiescent cells (Sawhney and Hall, 1992) was demonstrated (Papantoniou et al 2004; Papantoniou et al 2005). Papantoniou et al (2004) showed that the proliferative activity is a major independent factor affecting 99m Tc-(V)DMSA uptake in breast cancer as determined by Ki-67 expression and suggested that 99m Tc-(V)DMSA uptake can be of clinical significance as an in vivo indicator of cell proliferation.…”
Section: Introductionmentioning
confidence: 99%